Theoretical Foundations of the Study of Cultural Industries in the Light of Modern Humanitarianism - Dyakova, Tamara (Slavica, 2022)
The paper defines new perspectives of the study of cultural industries by the humanities. Cultural, philosophical and socioeconomic theories of the last century, which have entered our active academic life, are considered as the basic points of departure. The author considers the problem of humans and those cultural changes which contribute to the harmonization of ontological, axiological and aesthetic bases of  their existence in modern society.